Atomic layer deposited TiO2 nanofilm on titanium implant for reduced the release of particles - Zhao, Xiangyu; Zhang, Xiaoxuan; Zhou, Zilan; Meng, Fanchun; Liu, Ruilin; Zhang, Mengyuan; Hao, Yujia; Xie, Qingpeng; Sun, Xiaojun; Zhang, Bin; Wang, Xing (Frontiers in Bioengineering and Biotechnology, 2024)
Titanium implants are widely used in surgery due to their excellent biocompatibility and mechanical properties. However, excessive release of titanium species can cause implant failure. To address this issue, we explored atomic layer deposition (ALD) as a coating technology. Despite being underexplored in medical implantation, ALD stands out for its precise and conformal nature. We introduced titanium dioxide (TiO2) films onto implant surfaces using ALD for the first time. Our study focused on mitigating titanium species release and involved friction, electrochemical corrosion, and corrosion resistance experiments. Results demonstrated that the TiO2 film substantially reduced particle and ion release, offering remarkable friction resistance and low corrosion rate. Moreover, film performance was tied to ALD cycle count, showing improvements with more cycles and further reduction in titanium species release. This study underscores the potential of ALD-deposited TiO2 films to effectively minimize titanium species release, with correlation to ALD cycle count.